Pengaruh atribut usia dan jenis kelamin dosen terhadap pemberian evaluasi oleh mahasiswa - Nur Julqurniati; Jefri Setiawan; Winny Aisyah; Sofyan Hadi Surya (Jurnal Ilmiah Psikologi Terapan, 2021)
The practice of giving evaluations from students to lecturers is often the moment when the halo effect occurs. Sex and age as individual attributes contribute to positive or negative evaluations of teaching evaluations. The purpose of this study is whether the attributes of age and sex interact with the halo effect in giving evaluations from students to lecturers. This research uses a one-shot case study with an online between-subjects design. One hundred twenty participants were divided into four groups. Each group evaluates 1 of 4 different photos (young men, older men, young women, and older women) labeled with the identity as a lecturer. The results of multiple linear regression analysis show: (1) The sex of the lecturer has no effect on student evaluation (F=0.730, p=0.395); (2) Lecturer age has no effect on student evaluation (F=0.587, p=0.445); (3) The interaction of sex and age has no effect on student evaluation (F=0.649, p=0.525). The sex and age of the lecturer do not affect the evaluation by students. The halo effect did not occur in the students in this study.